Stripping voltammetric detection of insulin at liquid–liquid microinterfaces in the presence of bovine albumin - O'Sullivan, S.; De Eulate, E.; Yuen, Y.; Helmerhorst, Erik; Arrigan, Damien (Royal Society of Chemistry, 2013)
Electrochemistry at the interface between two immiscible electrolyte solutions (ITIES) provides a platform for label-free detection of biomolecules. In this study, adsorptive stripping voltammetry (AdSV) was implemented at an array of microscale ITIES for the detection of the antidiabetic hormone insulin. By exploiting the potential-controlled adsorption of insulin at the ITIES, insulin was detected at 10 nM via subsequent voltammetric desorption. This is the lowest detected concentration reported to-date for a protein by electrochemistry at the ITIES. Surface coverage calculations indicate that between 0.1 and 1 monolayer of insulin forms at the interface over the 10 – 1000 nM concentration range of the hormone. In a step toward assessment of selectivity, the optimum adsorption potentials for insulin and albumin were determined to be 0.900 V and 0.975 V, respectively. When present in an aqueous mixture with albumin, insulin was detected by tuning the adsorption potential to 0.9 V, albeit with reduced sensitivity. This provides the first example of selective detection of one protein in the presence of another by exploiting optimal adsorption potentials. The results presented here provide a route to the improvement of detection limits and achievement of selectivity for protein detection by electrochemistry at the ITIES.